ANALISIS SISTEM PENGENDALIAN INTERNAL (STUDI KASUS PADA BAITUL MAL ACEH SELATAN) BERBASIS COSO - Silfira, Tia; Aliamin, Aliamin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
The purpose of this study is to describe how COSO became part of the internal control system in Baitul Mal Aceh Selatan. Both primary and secondary data were used in this study. The primary data came from interviews with resource people, while the secondary data came from the archives of Baitul Mal Aceh Selatan. This study used descriptive analysis models. The results of this study indicated that Baitul Mal Aceh Selatan has not adhered to the general requirements for financial statements. This entity has not followed some of the regulations that have been set. It has not placed employees based on their expertise and education. It also does not possess adequate facilities and infrastructure to support the agency performance. Moreover, it revealed that the internal control system was undocumented in the form of flow charts or others. This meant that several weaknesses in internal control had not been fully addressed.